Long-term effects of cardiac rehabilitation after heart valve surgery - results from the randomised CopenHeartVR trial. (31st December 2022) - Sibilitz, Kirstine L.; Tang, Lars Hermann; Berg, Selina Kikkenborg; Thygesen, Lau Caspar; Risom, Signe Stelling; Rasmussen, Trine Bernholdt; Schmid, Jean-Paul; Borregaard, Britt; Hassager, Christian; Køber, Lars; Taylor, Rod S.; Zwisler, Ann-Dorthe
Abstract: Aims . The CopenHeartVR trial found positive effects of cardiac rehabilitation (CR) on physical capacity at 4 months. The long-term effects of CR following valve surgery remains unclear, especially regarding readmission and mortality. Using data from he CopenHeartVR Trial we investigated long-term effects on physical capacity, mental and physical health and effect on mortality and readmission rates as prespecified in the original protocol. Methods . A total of 147 participants were included after heart valve surgery and randomly allocated 1:1 to 12-weeks exercise-based CR including a psycho-educational programme (intervention group) or control. Physical capacity was assessed as peak oxygen uptake (VO2 peak) measured by cardiopulmonary exercise testing, mental and physical health by Short Form-36 questionnaire, Hospital Anxiety and Depression Scale, and HeartQol. Mortality and readmission were obtained from hospital records and registers. Groups were compared using mixed regression model analysis and log rank test. Results . No differences in VO2 peak at 12 months or in self-assessed mental and physical health at 24 months (68% vs 75%, p = .120) was found. However, our data demonstrated reduction in readmissions in the intervention group at intermediate time points; after 3, 6 (43% vs 59%, p = .03), and 12 (53% vs 67%, p = .04) months, respectively, but no significant effect at 24 months. Conclusions . Exercise-based CR after heart valve surgery reduces combined readmissions and mortality up to 12 months despite lack of improvement in exercise capacity, physical and mental health long-term. Exercise-based CR can ensure short-term benefits in terms of physical capacity, and lower readmission within a year, but more research is needed to sustain these effects over a longer time period. These considerations should be included in the management of patients after heart valve surgery.